The role of catchment scale and landscape characteristics for runoff generation of boreal streams - Laudon, Hjalmar; Sjöblom, Viktor; Buffam, Ishi; Seibert, Jan; Mörth, Magnus (Journal of hydrology (Amsterdam), 2007)
The effect of catchment scale and the influence of landscape characteristics on runoff generation were investigated during snow melt in 15 nested boreal streams within the Krycklan catchment in northern Sweden. We used detailed oxygen-18 analyses of soils from two characteristic landscape types, snow melt samples and water samples from 15 streams with subcatchments ranging in size from 0.03 to 67 km 2. The detailed process understanding that was derived from isotopic and hydrometric measurements at a wetland and a forest site, in combination with the stream monitoring, enabled the development of a conceptual framework that could explain the variability in hydrological pathways over a range of catchment scales. While the proportion of new or event water was over 50% in wetland dominated catchments, the event water contribution in forested catchments was between 10% and 30%. The results suggest a large degree of scale-independence of hydrological flow pathways during the snow melt period, controlled by the proportion of wetland and median subcatchment area, across three orders of magnitude in spatial scale. The results from this study highlighted the importance of different runoff generation processes in different landscape elements, an understanding that can be useful in disentangling the temporal dynamics in hydrology and biogeochemistry during snow melt episodes when moving from small headwater streams to catchment outlets.